The Degree of Applying Knowledge Management Processes from the Perspective of Faculty Members at Colleges of Educational Sciences in Private Jordanian Universities in the Capital Governorate - Dr. Monther Qasem Shboul (University of Science and Technology, Yemen, 2021)
The study aimed to identify the degree of applying processes of knowledge management at colleges of educational sciences in private Jordanian universities in the Capital Governorate from the perspective of faculty members, and the effect of gender, academic rank and experience variables on the degree of application. To achieve this, the analytical descriptive survey method was used, and a questionnaire was developed and included (25) items, covering three dimensions: knowledge generation, knowledge storage, knowledge transfer, and knowledge application. The questionnaire was distributed to as ample of (77) faculty members in the college of educational sciences in private universities in the capital governorate (Al-Zaytouna, the Middle East, Al-Isra and Petra) during the academic year 2018/2019. The results showed that the degree of application of knowledge management processes by colleges in the field of knowledge generation and knowledge transfer were medium (2.07) and (1.91), while the degree of application in the two fields of knowledge application and knowledge generation was low with means of (1.64) and (1.40). Results also showed that there were no statistically significant differences at (α<0.05) on all domains of knowledge management attributed to the variable of sex. There were statistically significant differences at (α<05.0) for the domains of knowledge management processes, all attributable to the variable of academic rank. However, there were no statistically significant differences at (α<05.0) in the degree of applying knowledge management processes among faculty members attributed to the variable of experience in all majors. It can be concluded that the degree of applying knowledge management processes at Colleges of Educational Sciences in private Jordanian universities in the Capital Governorate varied between medium and low. Therefore, the study recommended that knowledge management processes be adopted by Jordanian private universities in the Capital Governorate.